Secret Seven on the Trail [anglicky] / 4 - Blyton, Enid, 1897-1968; Brook, George (London : Hodder Children's Books, 2009)
Is something mysterious happening at Tigger´s Barn? Peter thinks it´s a hoax. Then Jack overhears an extraordinary conversation which leads the Seven on the trail of adventure!
Keywords: detektívky, trilery; Detective stories; cudzojazyčná literatúra; čítanie je IN (11+)